A meta-analysis reveals mostly neutral influence of scattered trees on pasture yield along with some contrasted effects depending on functional groups and rainfall conditions - Rivest, David; Paquette, Alain; Moreno, Gerardo; Messier, Christian (Agriculture, Ecosystems & Environment, 2013)
Scattered trees occurring throughout farmland matrix are prominent features of many human-dominated landscapes around the world, especially in livestock grazing systems. They are keystone structures that may play important roles in maintaining ecosystem functions, services, and farmland biodiversity. However, scattered trees in agricultural landscapes are declining worldwide due to intensive land use. They are often perceived by farmers as having negative impacts on agricultural production. Large-scale assessments in different biomes of agricultural yield in scattered tree ecosystems remain rare. Filling this knowledge gap may help improve decision-making regarding the value of scattered trees in agricultural landscapes. Using meta-analysis, we found that, across four tree functional groups (deciduous, Eucalyptus, N2-fixing, evergreen oak), mature scattered trees do not compromise pasture yield. The sign and magnitude of scattered tree effects on pasture yield did vary, however, among tree functional groups and according to precipitation levels. Our study suggests that, as drought pressure increases abiotic stress, tree facilitation by N2-fixing trees, and competition by Eucalyptus, will become the more common interactions between scattered trees and pasture. Management options exist to conserve and restore scattered trees in agricultural landscapes, but new policies are required to support their widespread adoption by farmers.
Keywords: Abiotic stress; Agroforestry; competition; Facilitation; Tree functional groups; tree-pasture interaction

Belowground competition for nutrients in shrub-encroached Mediterranean dehesas - Rivest, David; Rolo, Víctor; López-Díaz, M Lourdes; Moreno, Gerardo (Nutrient Cycling in Agroecosystems, 2011)
Managing multilayered silvopastoral systems such as Mediterranean dehesas requires the study of nutrient resource partitioning among coexisting species and determination to what extent soil nutrients are limiting plant growth. We determined the effects of NPK fertilisation maintained over two consecutive years on dry matter production and nutritional status of pasture (herbaceous) species, two shrub species and Quercus ilex L. in two silvopastoral sites with different shrub-layer species. We selected two prominent Mediterranean shrub species that vary in their speciﬁc ecological strategies: a N2-ﬁxing and sparse deep-rooting shrub (Retama sphaerocarpa (L.) Boiss, Retama site), and a dense shallow-rooting shrub (Cistus ladanifer L., Cistus site). Fertilisation signiﬁcantly (P B 0.05) increased pasture dry mass by 460% and 1,090% in the Retama and Cistus sites, respectively. Nitrogen uptake by pasture species was most stimulated in both sites, and was the major limiting nutrient for this group. At the Cistus site, fertilisation signiﬁcantly increased leaf dry mass of Q. ilex by 53%, but no signiﬁcant effect was found at the Retama site. There were no signiﬁcant effects of fertilisation treatments on dry mass and nutrient status of Retama cladodes and Cistus leaves. Vector analysis revealed that the magnitude of relative changes in nutrient uptake and dry matter production of pasture in response to fertilisation was markedly higher than that of Q. ilex, R. sphaerocarpa and C. ladanifer, suggesting high competitive ability of pasture species for soil nutrients. Results suggest that patterns of soil nutrient partitioning are site-speciﬁc and, thus, likely depend on the dominant species in the shrub layer
Keywords: Cistus ladanifer; Dry matter production; Native pasture; Nutrient uptake; Quercus ilex; retama sphaerocarpa; Silvopastoral systems

Shrub encroachment in Mediterranean silvopastoral systems: Retama sphaerocarpa and Cistus ladanifer induce contrasting effects on pasture and Quercus ilex production - Rivest, David; Rolo, Víctor; López-Díaz, Lurdes; Moreno, Gerardo (Agriculture, Ecosystems & Environment, 2011)
Silvopastoral systems are threatened worldwide by progressive loss of either tree cover or herbaceous cover due to lack of tree regeneration and shrub encroachment, respectively. Grazed Mediterranean open woodlands, as Iberian dehesa, are an outstanding example of silvopastoral system where shrub encroachment has been proposed as an effective means to facilitate tree seedling recruitment and ensure the system persistence. Shrubs also may interact with pasture understorey and tree overstorey, thereby affecting the overall system productivity. We tested the effects of shrub encroachment on pasture yield, tree growth and acorn production in years of contrasting rainfall in Quercus ilex L. dehesas of centralwestern Spain.We compared the effects oftwo prominentMediterranean shrub species that differ in their ecological strategies: a N2-ﬁxing and sparse deep-rooting shrub (Retama sphaerocarpa (L.) Boiss), and a dense shallow-rooting shrub (Cistus ladanifer L). In intermediate and dry years, pasture yield beneath tree canopy was lower by 21–35% than in open grassland. Pasture yield beneath tree canopy was not signiﬁcantly affected during the wet year. C. ladanifer encroachment signiﬁcantly reduced pasture yield by 68–98%, tree growth by 17–29%, and acorn yield by 6–44%. In contrast, R. sphaerocarpa signiﬁcantly increased pasture yield by 11–157% and tree growth by 6–13%, but had a neutral effect on acorn yield. Our results suggest that pasture is more sensitive to shrub encroachment and annual rainfall variation than is Q. ilex. The importance of C. ladanifer competition and R. sphaerocarpa facilitation on pasture yield increased in the driest year. We conclude that the sign and intensity of shrub encroachment effects on pasture and tree production in Mediterranean dehesas are species-speciﬁc and depend on temporal variation as a function of climate.
Keywords: acorn; Agroforestry; competition; Dehesa; Facilitation; Overstorey–understorey interactions